2007
DOI: 10.1002/chem.200700069
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Characterization, and Electrochemical Behavior of the Palladium–Hydride Cluster [Pd3(dppm)33‐CO)(μ3‐H)]+ (dppm=Bis(diphenylphosphinomethane)

Abstract: Addition of formate on the dicationic cluster [Pd(3)(dppm)(3)(mu(3)-CO)](2+) (dppm=bis(diphenylphosphinomethane) affords quantitatively the hydride cluster [Pd(3)(dppm)(3)(mu(3)-CO)(mu(3)-H)](+). This new palladium-hydride cluster has been characterised by (1)H NMR, (31)P NMR and UV/Vis spectroscopy and MALDI-TOF mass spectrometry. The unambiguous identification of the capping hydride was made from (2)H NMR spectroscopy by using DCO(2) (-) as starting material. The mechanism of the hydride complex formation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…[33][34][35][36][37] As expected, a transition metal centre with a d 10 Å), where the corresponding anti-bonding skeletal molecular orbitals are also fully occupied. 38 With regards to the unimolecular fragmentation chemistry, the calculations indicate that the first loss of the ligand, L (eqn (12)), from [Ag 3 (H)(BH 4 )L Me 3 ] + results in transferring the hydride to Ag 2 and causes this centre to adopt a mainly linear structure with a very weak interaction with Ag 1 (Fig. 5).…”
Section: Structural Characterization Of (1) By Esi/ms Nmr and Ir Spementioning
confidence: 99%
“…[33][34][35][36][37] As expected, a transition metal centre with a d 10 Å), where the corresponding anti-bonding skeletal molecular orbitals are also fully occupied. 38 With regards to the unimolecular fragmentation chemistry, the calculations indicate that the first loss of the ligand, L (eqn (12)), from [Ag 3 (H)(BH 4 )L Me 3 ] + results in transferring the hydride to Ag 2 and causes this centre to adopt a mainly linear structure with a very weak interaction with Ag 1 (Fig. 5).…”
Section: Structural Characterization Of (1) By Esi/ms Nmr and Ir Spementioning
confidence: 99%
“…Since 2005 many other systems have been investigated. These include, but are not limited to, porphyrins and phthalocyanines,26–37 other nitrogen heterocycles,26, 38–46 other nitrogen ligands,47–53 metallocenes/aryl ligands,26, 54–60 phosphorus ligands,26, 44, 57, 59, 61–63 hydrazones,64 carboxylates,51, 54, 65 thiophenes,66, 67 acetylacetonates,59, 68 ethers,69, 70 polyynes/cumulenes,71 acetohydrazides,72 octreotate,73 tripsalen,74 thiols75 and quinolates 76. Successfully characterised compounds have contained, but are not limited to, magnesium,37 the first‐row transition metals in general,63, 68 specifically vanadium,59 chromium,74 manganese,28, 74 iron,26, 35, 40, 54, 59, 60, 63, 66, 74 cobalt,28, 29, 31, 33, 34, 40, 42, 64, 72 nickel,29, 33, 40, 64, 67, 72 copper,26, 29, 31, 33, 34, 39, 52, 64, 71, 72 zinc,26, 28, 29, 31–34, 40, 45, 48, 55, …”
Section: A Brief Historymentioning
confidence: 99%
“…Successfully characterised compounds have contained, but are not limited to, magnesium,37 the first‐row transition metals in general,63, 68 specifically vanadium,59 chromium,74 manganese,28, 74 iron,26, 35, 40, 54, 59, 60, 63, 66, 74 cobalt,28, 29, 31, 33, 34, 40, 42, 64, 72 nickel,29, 33, 40, 64, 67, 72 copper,26, 29, 31, 33, 34, 39, 52, 64, 71, 72 zinc,26, 28, 29, 31–34, 40, 45, 48, 55, 64, 65, 72 gallium,26, 42 the Group 4 metals,58 ruthenium,26, 44, 46, 53, 57, 73 rhodium,26 palladium,28, 41, 49, 50, 53, 55, 61–63, 67 silver,28, 29, 52, 71 cadmium,40, 43, 47, 72 indium,42 tin,38, 51, 54, 69, 70 rhenium,26 osmium,26 iridium,39, …”
Section: A Brief Historymentioning
confidence: 99%
“…Catalysts of this type may range from long established systems such as Wilkinson's catalyst for alkene hydrogenation 13 to multinuclear clusters with known or potential use for the catalysis of hydrogen transfer reactions. 14,15 Solution 1 H NMR spectroscopic studies of MesPdH suggested the occurrence of a uxional process, which was thought to involve the hydride ligand exchanging between the palladium centres (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies on palladium hydride clusters have shown/ suggested that hydride transfer processes between metal centres can occur either with the Pd-Pd bond remaining intact, or with cleavage of the Pd-Pd via a Pd-H-Pd geometry. 14,15 These studies are mostly based on the interpretation of solution phase uxionality investigated by variable temperature NMR spectroscopy. The presence of good NMR probes in the clusters, phosphine ligands, can be invaluable in discriminating between mechanistic pathways.…”
Section: Introductionmentioning
confidence: 99%